Machine Learning Models for Bank failure Classification using different techniques to deal with imbalanced dataset - Santos, Gustavo Medeiros Ferreira dos (2021)
Dissertação (mestrado) — Universidade de Brasília, Faculdade de Economia, Administração e Contabilidade, Departamento de Economia, Programa de Pós-Graduação em Ciências Econômicas, 2021.